2015
DOI: 10.1037/a0037858
|View full text |Cite
|
Sign up to set email alerts
|

Reflective functioning moderates the association between perceptions of parental neglect and attachment in adolescence.

Abstract: Preliminary evidence suggests that reflective functioning (RF), or the ability to understand that mental states underlie behavior in the self and others (also called mentalizing), appears to be a protective factor against the development of psychopathology among adults who have experienced early abuse and neglect. The associations among early adverse experiences, RF, and attachment security have yet to be examined in adolescence. The aim of the present study was to evaluate whether RF moderates the link betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 37 publications
(69 reference statements)
2
40
0
2
Order By: Relevance
“…The proportion of disorganized attachment in the present sample (23%) coincides with results from a meta-analysis with 6,000 mother-child dyads from various ethnic, socioeconomic, and cultural backgrounds (20.4%) [16]. The RF in the present sample (mean = 3.43) replicates values from Borelli et al [83], who reported a mean RF of 3.2 in their sample of 84 adolescents, which is a lower RF value than in adult samples. Values of childhood maltreatment coincide with German and American prevalence rates [2,24].…”
Section: Discussionsupporting
confidence: 88%
“…The proportion of disorganized attachment in the present sample (23%) coincides with results from a meta-analysis with 6,000 mother-child dyads from various ethnic, socioeconomic, and cultural backgrounds (20.4%) [16]. The RF in the present sample (mean = 3.43) replicates values from Borelli et al [83], who reported a mean RF of 3.2 in their sample of 84 adolescents, which is a lower RF value than in adult samples. Values of childhood maltreatment coincide with German and American prevalence rates [2,24].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, although adolescents are typically quite engaged with their own thoughts and perspectives, the ability to be reflective and insightful about how their own thoughts and emotions relate to their behaviors is generally less well-developed (Benbassat & Priel, 2012; Borelli et al, 2014). There are few studies of adolescent RF in the literature, and all of them described relatively low levels on the RF scale: Borelli and colleagues (2012), reported a mean level of 2.95 (1.1) in a low-risk sample of white European adolescent females; Ha and colleagues (Ha, Sharp, Ensink, Fonagy, & Cirino, 2013) reported a mean level of 3.15 (0.2) in teens with mental health diagnoses; and (Benbassat & Priel, 2012) found a mean level of 3.88 (1.1) in their normative sample of Israeli youth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reflective mother would be curious about and open to the reasons for her child’s distress, as opposed to simply trying to control his crying. The capacity to envision mental states in the self and other is thought to emerge slowly over the course of development, likely not emerging fully until adulthood (Borelli, Compare, Snavely, & Decio, 2014; Slade, Grienenberger, et al, 2005). …”
mentioning
confidence: 99%
“…Los promedios en hombres y mujeres indican que sus relatos presentan estados mentales tales como feliz, seguro, triste, confiado, pero sin una evidente capacidad de reflexionar en torno a ellos. Esto es relevante, debido a que la literatura señala que niveles más altos de FR se relacionan con un estilo de apego seguro y, por el contrario, niveles más bajos se asocian a experiencias traumáticas sin elaborar y a patrones de apego inseguro (Borelli et al, 2015;Ensink et al, 2016).…”
Section: Discussionunclassified
“…Las investigaciones en FR muestran claramente dos grandes focos de estudio, uno que considera el apego, parentalidad y desarrollo infantil y otro que revisa y desarrolla intervenciones basadas en mentalización para mejorar el funcionamiento reflexivo (Ensink, Bégin, Normandin & Fonagy, 2017;Steele & Steele, 2008). Las investigaciones que consideran el primer foco han demostrado el rol de la FR, ya sea como moderador o mediador, en la relación entre distintas variables, como el estilo de apego de la madre y el estilo de apego del hijo , los síntomas depresivos de la madre y los comportamientos parentales (Wong, 2012) y las experiencias de maltrato en la infancia de los padres y el estilo de apego adolescente (Borelli, Compare, Snavely & Decio, 2015). Los estudios que consideran el segundo foco, intervenciones psicoterapéuticas basadas en mentalización, comenzaron para el tratamiento de trastornos de personalidad limítrofe , ampliándose luego a otras problemáticas, como, por ejemplo, intervenciones dirigidas a madres en prisión y sus hijos (Sleed, Baradon & Fonagy, 2013) y madres con abuso de sustancias (Suchman, Decoste, Rosenberger & McMahon, 2012), entre otros.…”
unclassified